Cytotoxic Clerodane Diterpenoids and Their Hydrolysis Products from Casearia nigrescens from the Rainforest of Madagascar - Williams, Russell B; Norris, Andrew; Miller, James S; Birkinshaw, Chris; Ratovoson, Fidy; Andriantsiferana, Rabodo; Rasamison, Vincent E; Kingston, David G. I (Journal of natural products (Washington, D.C.), 2007)
Bioassay-guided fractionation of the cytotoxic leaf and flower extract of Casearia nigrescens led to the isolation of four new clerodane diterpenoids, designated caseanigrescens A−D (1−4). These compounds were subject to hydrolysis to dialdehydes when stored in CDCl3. The structures of compounds 1−4 were determined using 1D and 2D NMR spectroscopy. All four compounds showed moderate cytotoxicity to the A2780 human ovarian cancer cell line, with an IC50 range of 0.83−1.4 μM.